2003
DOI: 10.2741/971
|View full text |Cite
|
Sign up to set email alerts
|

MHC restriction in allergic bronchopulmonary aspergillosis

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a rare complication in patients with asthma but more common in patients with cystic fibrosis. In the presence of the fungus Aspergillus fumigatus (Af) in the lower respiratory tract, patients mount a heightened IgG and IgE humoral response specific for Af antigens. Studies on ABPA have suggested a pathogenic role for antigen specific CD4+ Th2 like T lymphocytes producing increased levels of IL-4 and IL-5. MHC class II genes coding for highly polymorphic HLA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Communication between antigen presenting cells, or phagocytes such as MΦs, their environment and downstream adaptive immunity is essential for an effective immune response. Studies from the CF GWAS project have shown that there is a significant correlation between MHC class II polymorphisms in the HLA-DR and HLA-DQ regions and overall disease severity 89,92 , implicating differences in the capacity to communicate to T-cells and other adaptive immune cells. This is not unique to CF since there have been several instances of the association between specific MHC class II alleles and increased susceptibility or severity of inflammatory diseases, including allergic broncho-pulmonary aspergillosis, multiple sclerosis, rheumatoid arthritis, sarcoidosis, asthma and diabetes 93,94 .…”
Section: The Cf Phagocyte and Adaptive Communicationmentioning
confidence: 99%
“…Communication between antigen presenting cells, or phagocytes such as MΦs, their environment and downstream adaptive immunity is essential for an effective immune response. Studies from the CF GWAS project have shown that there is a significant correlation between MHC class II polymorphisms in the HLA-DR and HLA-DQ regions and overall disease severity 89,92 , implicating differences in the capacity to communicate to T-cells and other adaptive immune cells. This is not unique to CF since there have been several instances of the association between specific MHC class II alleles and increased susceptibility or severity of inflammatory diseases, including allergic broncho-pulmonary aspergillosis, multiple sclerosis, rheumatoid arthritis, sarcoidosis, asthma and diabetes 93,94 .…”
Section: The Cf Phagocyte and Adaptive Communicationmentioning
confidence: 99%
“…In one case series from India, 5 % of cases were found to be familial in nature [ 10 ]. The structural gene CFTR has been previously associated with ABPA [ 11 ], and small genetic association studies (involving ≤38 patients) have identified associations between ABPA and SNPs in the immune genes IL4R, IL10, TLR9, SFTPA2 and HLA (HLA-DR) [ 12 16 ], however, these results do not explain all cases of ABPA, and the immune mechanisms that underlie ABPA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…IL-4 is a critical mediator of B-cell switching to IgE as well as IgG4 synthesis. Markers around the IL-4 locus on chromosome 5q31.1 linked to a gene controlling IgE levels, GM allotypes on chromosome 14q32 and six HLA-DR2/5 subtypes on chromosome 6 reported to be of pathophysiological importance to ABPA [38] indicate a polygenic inheritance of the immune response.…”
Section: Association Between Gm and Km Allotypes And The Presence Of mentioning
confidence: 96%